Persistent memory despite rapid contraction of circulating T Cell responses to SARS-CoV-2 mRNA vaccination - Taus, Ellie; Hofmann, Christian; Ibarrondo, F. Javier; Gong, Laura S.; Hausner, Mary Ann; Fulcher, Jennifer A.; Krogstad, Paul; Kitchen, Scott G.; Ferbas, Kathie G.; Tobin, Nicole H.; Rimoin, Anne W.; Aldrovandi, Grace M.; et al. (Frontiers in Immunology, 2023)
While antibodies raised by SARS-CoV-2 mRNA vaccines have had compromised efficacy to prevent breakthrough infections due to both limited durability and spike sequence variation, the vaccines have remained highly protective against severe illness. This protection is mediated through cellular immunity, particularly CD8+ T cells, and lasts at least a few months. While several studies have documented rapidly waning levels of vaccine-elicited antibodies, the kinetics of T cell responses have not been well defined. In two persons receiving primary vaccination, tightly serially evaluated frequencies of anti-spike CD8+ T cells using interferon (IFN)-γ ELISpot measurements revealed strikingly short-lived responses, peaking after about 10 days and becoming undetectable by about 20 days after each dose. This pattern was also observed in cross-sectional analyses of persons after the first and second doses during primary vaccination with mRNA vaccines. In contrast, cross-sectional analysis of COVID-19-recovered persons using the same assay showed persisting responses in most persons through 45 days after symptom onset. Cross-sectional analysis using IFN-γ intracellular cytokine staining (ICS) of peripheral blood mononuclear cells (PBMCs) from persons 13 to 235 days after mRNA vaccination also demonstrated undetectable CD8+ T cells against spike soon after vaccination, and extended the observation to include CD4+ T cells. However, ICS analyses of the same PBMCs after culturing with the mRNA-1273 vaccine in vitro showed CD4+ and CD8+ T cell responses that were readily detectable in most persons out to 235 days after vaccination. Overall, we find that detection of spike-targeted responses from mRNA vaccines using typical IFN-γ assays is remarkably transient, which may be a function of the mRNA vaccine platform with perhaps a contribution of the spike protein as an immune target. However, robust memory, as demonstrated by capacity for rapid expansion of T cells responding to spike, is maintained at least several months after vaccination. This is consistent with the clinical observation of vaccine protection from severe illness lasting months. The level of such memory responsiveness required for clinical protection remains to be defined.